Significant Pathologic Response Following Neoadjuvant Therapy and Curative Resection in Patients With Rectal Cancer: Surgical and Oncological Outcomes From a Retrospective Cohort Study - Fatemeh Shahabi; Majid Ansari; Khadijeh Najafi Ghobadi; Abolfazl Ghahramani; Amiresmaeil Parandeh; Maryam Saberi‐Karimian; Ala Orafaie; Abbas Abdollahi (Cancer Reports, 2024)
ABSTRACT Aim This study evaluated surgical complication rates, recurrence‐free survival, overall survival (OS), and stoma status of patients with rectal cancer after significant pathologic response following neoadjuvant treatment and curative resection. Pathologic complete response (pCR) and near‐pCR patients constitute patients in our study. Methods Included was a retrospective cohort study of patients with rectal cancer who were diagnosed between July 2011 and September 2022 and who underwent neoadjuvant therapy and surgical resection. Results Of 696 patients with rectal cancer, 149 (21.4%) cases achieved significant pathologic response. During the 64 (70.5) months of follow‐up, recurrence occurred in 16.1% of patients and distant metastases account for the majority of them. Age (p = 0.014) and receiving adjuvant chemotherapy (p = 0.016) were significantly related to the occurrence of recurrence. The five‐year recurrence‐free survival (RFS) and OS rates were obtained at 83% and 87%, respectively. Although age and surgical technique were significant factors in univariate Cox regression analysis, none of the candidate variables were significant prognostic factors for RFS in the multiple models. The risk of surgical complications remained in these patients. The most frequent complication attributed to infection (20.8%). Despite the 24.8% presence of permanent stoma at primary surgery, more than 50% of our patients lived without stoma at the last follow‐up. Conclusion Our recurrence rate was about 16%, and it was related to age and adjuvant chemotherapy. These patients achieved over 80% rates of five‐year RFS and OS. No significant prognostic factors were found on RFS in the multivariable model. As a matter of course, the risk of surgical complications and permanent stoma has still remained in these patients.